A Formalist Approach to Religious Imagery in The Chronicles of Narnia: The Lion, The Witch and The Wardrobe by C. S. Lewis - Sulaiman, Firosyan Fittanasuqi; Munjid, Achmad (Universitas Gadjah Mada, 2024)
One of the most popular novels written for children is The Chronicles of Narnia: The Lion, The Witch and The Wardrobe by C. S. Lewis (2005). However, this novel is controversial amongst critics because it contains religious symbols. This research argues that The Chronicles of Narnia: The Lion, The Witch and The Wardrobe has its way of presenting religious symbols implicitly therefore children can enjoy reading it. Thus, this research aims to examine the effective presentation of religious symbols in the novel. This research uses the Formalism approach. To support the analysis, the researcher uses library research as the method with the religious symbols found in the novel as the primary data and the books and journals written by experts as the secondary data. The result of this research is The Chronicles of Narnia: The Lion, The Witch and The Wardrobe presented religious symbols through the characters of children, role models, central subjects and important events of the story of the novel.